Applying psychology to criminal justice - Carson, David (Wiley, 2007)
Psychology and law : a science to be applied / David Carson, Becky Milne, Francis Pakes, Karen Shalev and Andrea Shawyer -- Identification / Ronald P. Fisher & Margaret C. Reardon -- Behavioural science and the law : investigation / John G. D. Grieve -- Investigative interviewing: the role of research / Becky Milne, Gary Shaw and Ray Bull -- Credibility assessments in a legal context / Aldert Vrij -- Fact-finding and evidence / Jenny McEwan -- A psychology and law of fact-finding / David Carson -- Criminal responsibility / Susan Dennison -- Criminal thinking / Emma Palmer -- The mentally disordered offender : disenablers for the delivery of justice / Jane Winstone and Francis Pakes -- Decision making in criminal justice / Edie Greene and Leslie Ellis -- A behavioral science perspective on identifying and managing hindsight bias and unstructured judgment : implications for legal decision-making / Kirk Heilbrun and Jacey Erickson -- To decide or not to decide: decision making and decision avoidance in critical incidents / Marie Eyre and Laurence Alison -- Processes: proving guilt, disproving innocence / David Carson -- The changing nature of adversarial, inquisitorial and islamic trials / Francis Pakes -- misapplication of psychology in court / Peter J. van Koppen -- Identifying liability for organizational errors / David Carson -- Applying legal concepts / David Carson, Becky Milne, Francis Pakes, Karen Shalev and Andrea Shawyer